Taguchi optimization of hardness and scratch adhesion strength of multilayer Ti/TiN coatings on Ti-51 at%Ni alloy deposited via magnetron sputtering technique. - Arudi, Ishiaka Shaibu (Elsevier Editora Ltda, 2023)
The near equiatomic Ti-51at %Ni alloy has excellent corrosion resistance, strength, shape memory and pseudo-elastic behaviour. However, it is lacking biocompatibility due to the release of hazardous Ni-ions when used as an implant. Thus, this research proposes optimizing the fabrication of multilayer Ti/TiN coating on Ti-51at %Ni alloy using magnetron sputtering. The hardness and adhesion strength are crucial properties to sustain external bearing loads and to ensure the durability of the coating. The process parameters of magnetron sputtering were optimized using Taguchi method. The analysis showed that optimum adhesion strength was obtained at 370 W, 100 °C, 50 V and 5 sccm with respect to DC power, substrate temperature, bias voltage and nitrogen flow, respectively. Whereas, the optimum hardness was obtained at 370 W, 150 °C, 75 V and 5 sccm. The confirmation test evidenced the hardness and adhesion strength improvement by 6.83 % and 10.74 %, respectively. The results of the optimized substrate surface showed a dense and compact growth of the deposited layer with the absence of cracks and pores. Finally, this research demonstrated a promising durable multilayer Ti/TiN coating on Ti-51at %Ni for biomedical applications.